college algebra, Please help!!
posted by ladybug on .
How can the graph of g(x)=3square root x+3 be obtained from the graph of g(x)= 3 square root x?
A. shift the graph 3 units right
b. shift the graph 3 units up
c. shift the graph 3 units down
d. shift the graph 3 units left
I am having problems with the square roots. Can someone please help!!
the graph was shifted up 3 from the original graph that's all the question wants to know
Ladybug, you often tend to forget to put in brackets, so
if you shift
y = 3√x
" to the left 3 units" (d)
you get y = 3√(x+3)
whereas y = 3√x + 3 would have been "up 3 units" (b)